The Dimension of Religious Moderation in The Novel Mantiq At Tayr Fariduddin Attar (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
The discourse of religious moderation needs to be developed with a multidisciplinary approach, including linking it to the study of Sufistic literature. The literary work of the Sufi poetry novel, manthiq ath-thayr, by Fariduddin Attar is expected to be able to inspire the hearts of the readers regarding the importance of religious moderation in the context of nation and state. This article aims to reveal the dimensions of religious moderation in Fariduddin Attar's novel Manthiq Ath-Thayr. The method used in this researcgh is literatuary study with the novel Manthiq Ath-Thayr as the main reference by using a structuralist semiotic approach and Saussure’s theory of markers and signs. It was found that the semiotics in the novel Manthiq Ath-Thayr has strong dimension of values pluralism and religious tolerance. The dimensions of the pluralism value are represented by the three final valleys, namely pure oneness, amazement and absence, while the dimensions of the tolerance value are represented from the four initial valleys, namely search, love, wisdom and freedom. These two dimensions inspire the importance of traditionalizing differences in Indonesia to further strengthen national commitment, not the other way around.